Modern styles of interior design in the hotel sector: A systematic review - Abaalkhail, Mona Marmah (Journal of engineering sciences and information technology, 2022)
This study aimed to identify and comprehensively review studies related to modern styles of interior design with reference images and a deep learning model in the hotel sector. The author searched articles on interior design from databases published between 2000 and 2021. The systematic review included twenty articles based on predefined criteria for selection. A review of studies indicates that there are seven modern interior design styles namely: modern interior style, modern classic style, classic interior style, northern interior style, industrial interior style, rustic interior style, and green interior style. The interior design style is a useful concept, that has played an important role in helping people understand and communicate with interior design, as previous studies have focused on how the categories of interior design style are defined. Linear relationships between preference and complexity were found with preference and liking indicating that preference increases with lower complexity (simplicity) in line with higher impression. Moreover, contemporary style guestrooms got more positive reviews in all dimensions compared to traditional and classic style guestrooms.